Trypanosoma cruzi-specific IFN-γ-producing cells in chronic Chagas disease associate with a functional IL-7/IL-7R axis - Natale, María A (2018)
Fil: Natale, María A. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.